Development and psychometric validation of an emotional intelligence scale for elementary school students in Samarinda, Indonesia - Hamka; Sandi Rahma Widiastuti; Berliany Ath Thahirah; Reza Fahira; Naila Heldawati; Farah Salsa Febriana; Arfan Gaffar Kamal; Farida Rahayu; Desti Purnamasari (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study developed and evaluated an emotional intelligence scale for elementary school students using a quantitative design. We purposively sampled 206 students in grades 4–6 from Samarinda, Indonesia. To clarify, the process began with identifying emotional intelligence constructs, then formulating related indicators, and finally drafting initial scale items. Next, five experts reviewed the items to provide expert judgment. After incorporating feedback, we tested the instrument with the student participants. We assessed content validity with Aiken’s V, measured construct validity with Confirmatory Factor Analysis (CFA), and evaluated reliability using Cronbach’s Alpha. The model fit well (CFI = 0.936; TLI = 0.918; RMSEA = 0.069; SRMR = 0.068) and showed high reliability (α = 0.923). These results show the scale is valid, reliable, and suitable for educational use in assessing emotional intelligence in elementary students